Application of UPLC-MS/MS to Study Cellular Pharmacokinetics of Seven Active Components of Cnidii Fructus Extracts - Bai, Yu; Ouyang, Huizi; Liu, Yang; Zuo, Fanjiao; Li, Caixia; Zhou, Shuting; Chang, Yanxu; He, Jun (Current Drug Metabolism, 2024)
BackgroundCnidii Fructus (CF) is a herbal medicine with pharmacological activities such as antitumor, antiviral, antiallergic, antipruritic effects, and so on.ObjectiveIn this study, an ultra-high performance liquid chromatography/tandem mass spectrometry (UPLC-MS/MS) method was prepared and verified to measure the concentrations of seven analytes (bergapten, xanthotoxol, xanthotoxin, imperatorin, osthole, isopimpinellin, isoimperatorin) in HepG2 cells.MethodsThe separation of seven analytes was performed on an ACQUITY UPLC® BEH C18 column (2.1×100 mm, 1.7 μm) with a gradient mobile phase system of 0.1% formic acid/water and acetonitrile.ResultsThe CV of analytes was within 7.77%, and the bias was in the range of -5.43%-3.84%. The matrix effects of analytes ranged from 92.95% to 104.58%, and the extraction recoveries ranged from 76.45% to 104.69%. The relative standard deviation of stability results was less than 8.21%, indicating that seven analytes were stable.ConclusionThe method was successfully applied to the determination of the content of seven analytes of CF extracts by UPLC-MS/MS, and the results will provide a reference for the cellular pharmacokinetics of CF.
Keywords: coumarin